Parental Interpersonal Communication In Overcoming Children's Anxiety When Participating In Online Learning - Abrar Adhani; Akhyar Anshori; Nurhasanah Nasution (CV. Publikasi Indonesia, 2021)
The government's policy on the learning system through network media during the COVID-19 pandemic has pros and cons in the community. For those who are pro against the policy, it is based on the consideration that health is far more important than gaining knowledge through face-to-face in order to anticipate the spread of the corona virus. Meanwhile, those who are against think that learning activities through the network will have an impact on the development of students/children in developing knowledge and the interaction process that is not going well during the pandemic. This study aims to determine how the influence of parental interpersonal communication on children's anxiety during online learning during the Covid-19 pandemic. The approach used in this study is a quantitative approach with data collection carried out through questionnaires to 400 respondents. The data obtained were then analyzed using SPSS 25.0 software for windows. The results of the study found that interpersonal communication between parents and children carried out during the COVID-19 pandemic related to children's education greatly influenced the development of children's education. The learning system that takes place in a network, makes parents and students experience very significant obstacles. In addition, the learning process through the network also affects the psychology of children's growth and development.